PERANCANGAN SUDU HORIZONTAL AXIS WIND TURBINE PADA KECEPATAN ANGIN 6-12 m/s - Dimas Dwi Atmaja Putra, (2020)
Wind is an example of renewable energy, the potential of wind energy in Indonesia is quite adequate, because the average wind speed can reach 3.5-12 m / s. In the Horizontal Axis Wind Turbine there are 3 types of blades that can be used where each blade has a match of the characteristics of the wind. Therefore a different design is needed so that the wind turbine can work optimally. The design is carried out with the help of software and has a turning radius of 1 m, the maximum length of the chord is 0.101 m and the angle of attack ranges from 2.5-7.5 °. Based on the results of the rotor simulation, the type of taper blade is capable of producing greater power compared to the 2 other types of inverse taper blades, and taper. The taper blade is capable of producing power of 1630 Watt at 750 rpm using the SG 6043 airfoil profile with 3 blades.